Emergency peripartum hysterectomy: a retrospective study of 7 years - Hoblidar, Suchith; K. S., Sunil Kumar; Desai, Ratnamala M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Emergency peripartum hysterectomy (EPH) is a rare but a lifesaving procedure done as a last resort to save life of mother. We conducted this study to know the incidence, leading causes, risk factors and complications of EPH. Methods: We conducted a retrospective analysis of all the patients who underwent EPH from January 2008 to December 2015 at SDMCM and H. All patients who underwent EPH from 22 weeks of gestation to 6 weeks postpartum were included in the study. Results: There were 21 emergency peripartum hysterectomies, with deliveries during the same period being 27271 and the rate of EPH was 0.7 per 1000 deliveries. Most common indication for EPH was uterine atony (38%), followed by uterine rupture (23.8%) and morbidly adherent placenta (19%). Most of the patients (47.6%) had previous cesarean deliveries. EPH was done following cesarean in 66.6%. Subtotal hysterectomy was done in 61.9%. Intra-operative urinary bladder injury was seen in 14.2% of the patients. Conclusions: Uterine atony and uterine rupture continues to be the most common causes for EPH in our population. Multiparity is an important risk factor among patients with rupture uterus. Cesarean delivery and repeat cesarean deliveries are the likely risk factors for EPH.